Acetic Anhydride as an Oxygen Donor in the Non‐Hydrolytic Sol–Gel Synthesis of Mesoporous TiO2 with High Electrochemical Lithium Storage Performances. Issue 18 (4th March 2019) - Wang, Yanhui; Kim, Sanghoon; Louvain, Nicolas; Alauzun, Johan G.; Mutin, P. Hubert
Abstract: An original, halide‐free non‐hydrolytic sol–gel route to mesoporous anatase TiO2 with hierarchical porosity and high specific surface area is reported. This route is based on the reaction at 200 °C of titanium(IV) isopropoxide with acetic anhydride, in the absence of a catalyst or solvent. NMR spectroscopic studies indicate that this method provides an efficient, truly non‐hydrolytic and aprotic route to TiO2 . Formation of the oxide involves successive acetoxylation and condensation reactions, both with ester elimination. The resulting TiO2 materials were nanocrystalline, even before calcination. Small (about 10 nm) anatase nanocrystals spontaneously aggregated to form mesoporous micron‐sized particles with high specific surface area (240 m 2 g −1 before calcination). Evaluation of the lithium storage performances shows a high reversible specific capacity, particularly for the non‐calcined sample with the highest specific surface area favouring pseudo‐capacitive storage: 253 mAh g −1 at 0.1 C and 218 mAh g −1 at 1 C (C=336 mA g −1 ). This sample also shows good cyclability (92 % retention after 200 cycles at 336 mA g −1 ) with a high coulombic efficiency (99.8 %). Synthesis in the presence of a solvent (toluene or squalane) offers the possibility to tune the morphology and texture of the TiO2 nanomaterials. Abstract : Nanocrystalline TiO2 materials : The reaction of Ti(O i Pr)4 with acetic anhydride at 200 °C leads to mesoporous nanocrystalline TiO2 with a hierarchical porosity and a very high specific surface area. This truly non‐hydrolytic sol–gel route involves the intermediate formation of Ti−OAc groups, which then condense with Ti−O i Pr groups, along with ester elimination. Evaluation of lithium storage performances shows a high reversible specific capacity, good cyclability and high coulombic efficiency (see figure; NS=no solvent, nc=non‐calcined, c=calcined, Comm=commercial).